Synthesis of Photochromic AgCl-Urethane Resin Composite Films - Hidetoshi Miyazaki; Hirochi Shimoguchi; Hisao Suzuki; Toshitaka Ota (Advances in Materials Science and Engineering)
AgCl-resin photochromic composite films were prepared using AgNO3, HCl-EtOH, CuCl2 solution, and a liquid-state urethane resin as starting materials. The obtained composite films showed a photochromic property. The rate of darkening of the composite film increased after mixing with CuCl2. The AgCl particle size in the film without heat treatment was 6–20 nm, and that of the heat-treated film was 25–80 nm; these results were confirmed using TEM observations. The fading rate of the film without heat treatment was higher than that of the heat-treated films.